Immunoglobulin G4-Related Disease: An Update - Al-Mujaini, Abdullah (Oman Med J, 2018)
Immunoglobulin G4-related disease (IgG4-RD) is an increasingly recognized immune-mediated condition comprised of a collection of disorders that share specific pathological, serological, and clinical features. IgG4-RD is a fibroinflammatory condition with a tendency to form tumors with inflammatory infiltrate with IgG4 rich plasma cells and elevation of serum IgG4, which may affect virtually every organ and tissue. IgG4-related ophthalmic disease may present as dacryoadenitis, myositis, or involvement of other orbital tissue. Hypophysitis or pachymeningitis may manifest as cranial neuropathies. The diagnosis of IgG4-RD is based on a typical clinical scenario, supportive laboratory test, expected radiological characteristics, and distinct histopathological and immunohistochemical features. Corticosteroids and immunosuppressives form the mainline treatment.